Fracture risk prediction in post-menopausal women with osteopenia and osteoporosis: preliminary findings - Nik Mohd Hatta, Nik Noor Kaussar; Md Isa, Muhammad Lokman; Nurumal, Mohd. Said; Daud, Azlina; Ibrahim, Muhammad; Sharifudin, Mohd Ariff; Draman, Samsul (Elsevier Doyma, 2017)
Objective: The study aims to identify the risk of obtaining a fracture among post-menopausal women with osteopenia and osteoporosis. Method: This work was a cross-sectional study involving a purposive sample of 87 post-menopausal women who attended the orthopedic and menopause clinics of Hospital Tengku Ampuan Afzan, Kuantan. The data were entered into the WHO fracture risk assessment tool (FRAX®) to predict major fracture and risk for hip fracture in 10 years’ time. Results: The mean age of the respondents was 61.6 years (SD = 7.9). Among the respondents, 50.6% had osteopenia and nearly half (48.3%) had osteoporosis. The mean number of menopausal years of the respondents was 11.9 (SD = 8.5), ranging between 1 and 44 years. The FRAX findings indicated 9.7% major osteoporotic fracture probability and 3.5% hip fracture probability, which were denoted as high risk. A Pearson correlation coefficient was computed to assess the relationship between menopausal years and the FRAX major osteoporotic fracture probability. A significant positive correlation was found between the two, but the correlation was weak (r = 0.581, n = 87, p < 0.001). Conclusions: The present findings indicate that menopausal years have a positive correlation with the risk of obtaining a fracture.